Penguatan Nilai Toleransi Siswa SD melalui Media Interaktif dan Partisipatif - Elvira Santoso; Jillian Eddy (Advances In Education Journal, 2025)
Diversity is a natural part of social life in Indonesia, so the value of tolerance needs to be taught from the elementary school level. Unfortunately, character education is often not effective enough in shaping tolerant attitudes in children, especially in environments that lack contextual and interactive learning methods. This community service activity aimed to instill the values of tolerance and anti-intolerance through an interactive, participatory, and experience-based learning approach. The program was carried out through a one-time school visit that involved students in various activities such as reflective games, cultural exploration using Google Earth, case study card games, and interactive quizzes. Observation results showed an improvement in students’ understanding of diversity and tolerant behavior, as seen from their active participation, social reflection, and willingness to express opinions. This activity shows that experience-based learning can be an effective strategy to help students internalize Pancasila values, especially tolerance. The findings emphasize the importance of creative, contextual, and enjoyable character education methods to support the development of an inclusive society from an early age.